Bilateral olecranon fracture in adult. A case report. - Zakaria@Mohamad, Zamzuri; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Mohamed Amin, Mohamed Azril; Awang, Mohd Shukrimi; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin (Faculty of Medicine, International Islamic University Malaysia, 2006)
We report a case of a 14 - year - old Malay male who fell at school and sustained bilateral olecranon fractures. He had undergone an open redu ction and tension band wiring to stabilize the fracture. Three months after the surgery, the movement of both his elbows was satisfactory